A Filter Algorithm with Inexact Line Search. (23rd February 2012) - Liu, Meiling; Li, Xueqian; Wu, Qinmin
Abstract : A filter algorithm with inexact line search is proposed for solving nonlinear programming problems. The filter is constructed by employing the norm of the gradient of the Lagrangian function to the infeasibility measure. Transition to superlinear local convergence is showed for the proposed filter algorithm without second-order correction. Under mild conditions, the global convergence can also be derived. Numerical experiments show the efficiency of the algorithm.